Augmented reality on students' academic achievement viewed from the creative thinking level - I Gusti Putu Asto Buditjahjanto; Juki Irfansyah (OmniaScience, 2023)
The use of computer applications as learning media has been widely used in the learning process. One such computer application is Augmented Reality. Augmented Reality has advantages in ease of use, media appeal, and mobility because it can be used on cell phones and tablets. Creative thinking is a skill that students need in solving problems in a learning process in the classroom. The research objective is to investigate the effect of augmented Reality on students' academic achievement viewed from the creative thinking level. MANOVA was used to analyze differences in cognitive and psychomotor learning outcomes between the experimental class using AR and the control class using PowerPoint. The results showed that learning media and creative thinking levels affect cognitive and psychomotor learning outcomes. Cognitive learning outcomes of students using AR are higher than student learning outcomes using PowerPoint. Meanwhile, the psychomotor learning outcomes of students using AR are higher than those using PowerPoint. The learning media significantly affects cognitive learning outcomes with a p-value = 0.007, while the creative thinking level significantly affects psychomotor learning outcomes with a p-value = 0.016.